Designing an Expert System for Diagnosing Otitis Disease Using Forward Chaining and Certainty Factor Methods - Muhammad Jufri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The ear is the five senses and is the external organ that most often interacts with external objects, the most common disturbance in the ear organs is an infection in the ear called otitis, otitis is an inflammation that causes an infection in the ear. Otitis itself has many types such as external, media, internal, and others. with research using an Expert System, utilizing the Forward Chaining and Certainty Factor methods, it is hoped that it can help patients to be able to consult the system, as appropriate to consult an ENT-KL specialist, with an accuracy of up to 94%.